Evaluation of Endoscopic Strip Craniectomy and Orthotic Therapy for Bilateral Coronal Craniosynostosis. Issue 2 (March 2019) - Williams, Conor T.; Segar, David J.; Naidoo, Sybill D.; Skolnick, Gary B.; Proctor, Mark R.; Smyth, Matthew D.; Patel, Kamlesh B.
Abstract : Background: Bilateral coronal craniosynostosis is the premature fusion of both coronal sutures. Traditionally, this condition is treated by frontal–orbital advancement (FOA). Endoscopic strip craniectomy with cranial orthotic therapy, which has gained popularity in treating single suture craniosynostosis, has recently been adapted for the treatment of bicoronal synostosis. There have been few studies documenting the outcomes of this treatment. The objective of this study is to compare the morphological outcomes of endoscopic strip craniectomy and FOA in patients with bicoronal synostosis. Methods: A retrospective case series was done on 24 patients with bilateral coronal synostosis treated with endoscopic strip craniectomy or FOA at 2 institutions. Patients with preoperative and 1-year postoperative computed tomography scans were included. Multiple measures of cranial shape and size were assessed: cephalic index, turricephaly index, basofrontal angle, circumference Z -score, and cranial vault volume Z -score. Results: The 2 groups were similar statistically in terms of morphology at preoperative scan. There were no statistical differences between the FOA group and endoscopic group at postoperative scan in any of the morphologic outcomes measured. Cranial vault volume Z -scores increased postoperatively in both the endoscopic ( P  < 0.001) and FOA ( P  = 0.034) groups. Conclusions: One year after repair there were no significant morphological difference between patients with bicoronal synostosis treated with the endoscopic approach and those treated by FOA.